2014
DOI: 10.3324/haematol.2013.103291
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab and three dexamethasone cycles provide responses similar to splenectomy in women and those with immune thrombocytopenia of less than two years duration

Abstract: Adults with newly diagnosed or persistent immunothrombocytopenia frequently relapse upon tapering steroids; adults and children with chronic disease have an even lower likelihood of lasting response. In adults with newlydiagnosed immunothrombocytopenia, two studies showed that dexamethasone 40 mg/day x four days and 4 rituximab infusions were superior to dexamethasone alone. Studies have also shown three cycles of dexamethasone are better than one and patients with persistent/chronic immunothrombocytopenia res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 33 publications
3
77
0
Order By: Relevance
“…The improved outcome for men in our study has not been reported in studies previously using rituximab either alone 19 or in combination with dexamethasone. 10 Our study suggests that male ITP patients may benefit from T-cell suppression, but this requires confirmation by further studies.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The improved outcome for men in our study has not been reported in studies previously using rituximab either alone 19 or in combination with dexamethasone. 10 Our study suggests that male ITP patients may benefit from T-cell suppression, but this requires confirmation by further studies.…”
Section: Discussionmentioning
confidence: 71%
“…7,8 Recent studies combining dexamethasone and rituximab in short courses have reported encouraging results. [9][10][11][12][13] We postulate that adding cyclosporine to this combination may induce a more enduring remission by also targeting T cells and thereby briefly suppressing all 3 immune cell types implicated in sustaining the pathogenic loop.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Later on, the combination of RTX and 3 cycles of dexamethasone showed apparently better efficacy than RTX alone or dexamethasone alone. 29 These conflicting findings indicate that the efficacy and safety of the combination of RTX with other drugs in the treatment of ITP needs further study. We hereby performed a multicenter prospective randomized controlled study in corticosteroid-resistant or relapsed ITP patients treated with either RTX 1 rhTPO or RTX alone, and we found that the combination yielded a significantly higher CR rate and shortened TTR compared with RTX alone but failed to show beneficial effect on the long-lasting response.…”
Section: Discussionmentioning
confidence: 99%
“…11,24,[29][30][31] In this study, the overall response rate in both groups was fairly high, which might be due to the generally short duration of ITP from diagnosis to enrollment. Age, gender, and the presence of autoantibodies were not associated with response rate or relapse in our study.…”
Section: Discussionmentioning
confidence: 99%
“…82 However, a randomized study that enrolled corticosteroid-resistant ITP patients with a median ITP duration of 37 weeks failed to demonstrate a higher rate of long-term responses with rituximab. 83 Thus, whether rituximab is able to induce long-term remissions of ITP, or whether studies suggesting that it may do so reflect the natural history of the disease, remains unresolved.…”
mentioning
confidence: 99%